Arsenic‐Rich Polyarsenides Stabilized by Cp*Fe Fragments. Issue 25 (16th May 2017) - Schmidt, Monika; Konieczny, David; Peresypkina, Eugenia V.; Virovets, Alexander V.; Balázs, Gabor; Bodensteiner, Michael; Riedlberger, Felix; Krauss, Hannes; Scheer, Manfred
Abstract: The redox chemistry of [Cp*Fe(η 5 ‐As5 )] (1, Cp*=η 5 ‐C5 Me5 ) has been investigated by cyclic voltammetry, revealing a redox behavior similar to that of its lighter congener [Cp*Fe(η 5 ‐P5 )]. However, the subsequent chemical reduction of1 by KH led to the formation of a mixture of novel Asn scaffolds with n up to 18 that are stabilized only by [Cp*Fe] fragments. These include the arsenic‐poor triple‐decker complex [K(dme)2 ][Cp*Fe(μ, η 2:2 ‐As2 )2 ] (2 ) and the arsenic‐rich complexes [K(dme)3 ]2 [(Cp*Fe)2 (μ, η 4:4 ‐As10 )] (3 ), [K(dme)2 ]2 [(Cp*Fe)2 (μ, η 2:2:2:2 ‐As14 )] (4 ), and [K(dme)3 ]2 [(Cp*Fe)4 (μ4, η 4:3:3:2:2:1:1 ‐As18 )] (5 ). Compound4 and the polyarsenide complex5 are the largest anionic Asn ligand complexes reported thus far. Complexes2 –5 were characterized by single‐crystal X‐ray diffraction, 1 H NMR spectroscopy, EPR spectroscopy (2 ), and mass spectrometry. Furthermore, DFT calculations showed that the intermediate [Cp*Fe(η 5 ‐As5 )] −, which is presumably formed first, undergoes fast dimerization to the dianion [(Cp*Fe)2 (μ, η 4:4 ‐As10 )] 2− . Abstract : The chemical reduction of [Cp*Fe(η 5 ‐As5 )] (1 ) with KH leads to a mixture of polyarsenic ligand complexes, such as [K(dme)2 ][Cp*Fe(μ, η 2:2 ‐As2 )2 ] (2 ), [K(dme)3 ]2 [(Cp*Fe)2 (μ, η 4:4 ‐As10 )] (3 ), [K(dme)2 ]2 [(Cp*Fe)2 (μ, η 2:2:2:2 ‐As14 )] (4 ), and [K(dme)3 ]2 [(Cp*Fe)4 (μ4, η 4:3:3:2:2:1:1 ‐As18 )] (5 ). Complexes4 and5 are the largest anionic polyarsenic ligand complexes reported thus far. Compound1 is therefore a powerful starting material for generating polyarsenic moieties.